Compassionate Love Scale Validation - Dinie Ratri Desiningrum; Fajrianthi Fajrianthi; Urip Purwono; Dewi Retno Suminar; Endang Retno Surjaningrum (International Journal Labs, 2022)
Compassionate love is an important concept in a relationship, defined as an attitude towards other people, both close others and foreign; contain feelings, cognitions, and behaviors that focus on caring, attention, tenderness, and orientation to support, help, and understand others. The purpose of this study is to validate Compassionate Love Scale (CLS) developed by Sprecher and Fehr. The method of translating into Indonesian refers to the International Test Commission. Confirmatory factor analysis (CFA) was conducted on data from 185 subjects (consisting of mothers and caregivers). The results show that the second order CFA measurement model is a model that is fit with CLS. The reliability of the three CLS dimensions is high based on Composite Reliability (CR) and Average Variance Extracted (AVE) values, namely: (1) tenderness and caring (0.895; 0.552); (2) acceptance and understanding (0.907; 0.594); and (3) helping and sacrifice (0.954; 0.749). In addition, CLS also fulfills convergent and discriminant validity. Thus, Compassionate Love Scale (CLS) translation results are a valid and reliable scale for use in Indonesia.